Notes on rattans (Arecaceae) from Vietnam - Henderson, A.; Dung, N. Q. (Phytotaxa, 2014)
Six rattan genera occur in Vietnam: Plectocomia, Plectocomiopsis, Myrialepis, Daemonorops, Calamus, and Korthalsia. Here we describe and illustrate one new species of Plectocomiopsis (P. songthanhensis), two of Daemonorops (D. brevicaulis, D. ocreata), and three of Calamus (C. parvulus, C. seriatus, C. yentuensis). Additionally we transfer two Calamus species, C. fissilis and C. nuichuaensis, to Daemonorops.